Manajemen Pemasaran Menggunakan Analisis SWOT Pada UMKM Guna Meningkatkan Daya Saing UMKM - Ronda Deli Sianturi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Micro, Small and Medium Enterprises (MSMEs) are currently experiencing quite difficult conditions amid the changing business environment and increasingly intense national or international business competition. MSMEs as one of the supporters of economic growth especially in Indonesia should receive more attention from the government, increasing the MSME sector and reducing poverty are indicators of the success of development specifically for countries with low capita incomes. One obstacle for SMEs is environmental factors, both internal and external environmental factors. Ignorance for MSME actors anticipates changes in the environment and does not have a marketing strategy that causes MSMEs to be less competitive compared to other products. SWOT analysis is an appropriate alternative to help MSMEs determine marketing strategies and anticipate changes in the business environment. Where the SWOT analysis can analyze Strengths, Weaknesses which are part of internal factors in MSMEs and Threats, Opportunities which are part of external factors or competitors. From this research, 4 marketing strategies were obtained for MSMEs to improve competitiveness, namely the MSME S-O Strategy to innovate, make products unique and utilize technology as a promotional and sales media. The W-O Strategy, MSMEs are required to always pay attention to the reluctance of market share and also consumers who demand MSMEs to continue to innovate on product value. S-T strategy, products produced by SMEs should have a characteristic value and provide protection to the product by making their own trademarks. The W-T Strategy, introduces products to areas outside the product cluster and the resulting products are packaged in an innovative way.